1995
DOI: 10.1002/jmv.1890450411
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to hepatitis C virus second envelope (HCV‐E2) glycoprotein: A new marker of HCV infection closely associated with viremia

Abstract: The second envelope protein (E2) of the hepatitis C virus (HCV) was cloned and expressed in Chinese hamster ovary (CHO) cells. This E2 glycoprotein was purified using ion exchange and lectin chromatography and used to construct an enzyme immunoassay for HCV E2 antibodies. The assay was shown to have good specificity, and detection of E2 antibodies was positively correlated (97.3%) to the presence of HCV RNA in serum and plasma. A high concordance between HCV 2.0 and E2 EIA reactivities was also observed. E2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
72
2

Year Published

1996
1996
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 36 publications
6
72
2
Order By: Relevance
“…Previous results have shown that truncated forms of E2 ending at amino acids 661,664,668,683,699,710 and 715 are secreted (Lesniewski et al, 1995 ;Matsuura et al, 1994 ;Nishihara et al, 1993 ;Selby et al, 1994). The size of the deletion did not affect the level of secretion, since truncated E2 glycoproteins ending at amino acids 661, 699, 710 and 715 were equally secreted (Selby et al, 1994), and we obtained similar results for truncated E2 glycoproteins expressed by vaccinia virus.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous results have shown that truncated forms of E2 ending at amino acids 661,664,668,683,699,710 and 715 are secreted (Lesniewski et al, 1995 ;Matsuura et al, 1994 ;Nishihara et al, 1993 ;Selby et al, 1994). The size of the deletion did not affect the level of secretion, since truncated E2 glycoproteins ending at amino acids 661, 699, 710 and 715 were equally secreted (Selby et al, 1994), and we obtained similar results for truncated E2 glycoproteins expressed by vaccinia virus.…”
Section: Discussionsupporting
confidence: 85%
“…Properly folded forms can be used in biochemical studies, such as defining the nature of E2 intramolecular disulfide bonds. Secreted HCV glycoproteins can also be used to study their interaction with the cell surface (Rosa et al, 1996), or for diagnostic purposes (Lesniewski et al, 1995). In this work, Sindbis and vaccinia virus recombinants were used to express full-length and carboxyterminally truncated forms of HCV glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were low viremic cases that could not be structural (core) and nonstructural HCV proteins. [13][14][15] However, our data indicate that while highly viremic genotyped. An explanation for such cases is infection with a unique viral genotype.…”
Section: Resultsmentioning
confidence: 91%
“…This is compatible with a few recent studies (62%), compared with 2 of the 70 patients with high using native E2/NS1 glycoprotein. [13][14][15] viremia of ¢10 6 copies/mL (3%). Serum HCV-RNA levIn previous studies, the E2/NS1 antibody response els expressed as log 10 (copy numbers of HCV RNA per was not quantitatively evaluated in relation to HCV mL serum) were significantly higher in E2/NS1 anti-replicative levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation